The Effectiveness of Sustainable City Development in the Creation of SDG's 11th Point through Slum Alleviation in Palembang City - Azhar, Azhar; Nisyak, Hoirun; Permatasari, Yuni; Putri, Cynthia Azhara (Universitas Medan Area, 2025)
The phenomenon of slum areas in several cities is a social dynamic due to high urbanization, limited land, and high land prices. Objectives This study analyzes the effectiveness of sustainable city development in creating SDG's point 11 through eradicating slums from the international regime of the United Nations to apply to national regulations and locus in the city of Palembang. The method used in this study is qualitative, descriptive, and exploratory by analyzing the influence and relationship between variables with empirical testing into a design to explore sustainable urban Development through alleviating slums in Palembang City. Furthermore, the data collection techniques used are literature studies and in-depth interviews with several parties directly related to the study. In this study, using the concept of international regime effectiveness, Arild Underdal has three phases in its implementation. First, output refers to the rules, programs, and organizations set by the PPB regarding the written concept of the SDGs and implemented by Indonesian member countries. Second, the Outcome: Palembang is a city that adjusts and implements these rules to achieve slum alleviation through SDG sustainable city development, point 11; Third, Impact, the level of success in overcoming the problems that are the basis for the formation of the UN regime regarding Development, where Indonesia has ratified it into a national law to cities in several provinces, including the creation of sustainable city development through sustainable areas and slum-free areas in Palembang City through the synergy of the Ministry of Public Works and Public Works and the Ministry of Environment.